Characterization of epididymal and testicular histologic lesions and use of immunohistochemistry and PCR on formalin-fixed tissues to detect Brucella canis in male dogs. (March 2021) - Camargo-Castañeda, Andrea M.; Stranahan, Lauren W.; Edwards, John F.; Garcia-Gonzalez, Daniel G.; Roa, Leonardo; Avila-Granados, Lisa M.; Hensel, Martha E.; Arenas-Gamboa, Angela M.
In male dogs, Brucella canis frequently causes epididymitis, ultimately resulting in testicular atrophy and infertility. Although B. canis predominantly affects the epididymis, the misleading term "orchitis" is still commonly used by clinicians. Of additional concern, diagnosis in dogs remains challenging because of variable sensitivity and specificity of serologic assays and fluctuations in bacteremia levels in infected dogs, reducing the sensitivity of blood culture. We describe here the histologic lesions in the scrotal contents of 8 dogs suspected of being infected with B. canis and clinically diagnosed with orchitis. We explored the possibility of using immunohistochemistry (IHC) and real-time PCR (rtPCR) in formalin-fixed, paraffin-embedded (FFPE) tissues to detect the presence of B. canis . Epididymitis of variable chronicity was identified in all 8 dogs, with only 3 also exhibiting orchitis. Using rtPCR, the presence of B. canis was identified in 4 of 8 dogs, with 3 of these 4 dogs also positive by IHC. These results suggest that rtPCR and IHC are promising techniques that can be used in FFPE tissues to detect B. canis when other detection techniques are unavailable. Additionally, accurate recognition of epididymitis rather than orchitis in suspect cases could aid in accurate diagnosis.